PERSEPSI FAKTOR-FAKTOR YANG MEMPENGARUHI PERFORMANCE KARYAWAN PT. THAMRIN BROTHERS SENTRAL YAMAHA KOTA BENGKULU - Fauzan Fauzan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
Research to analiyze the effect of Leadership, Reward and Punishment on Employee Performance in PT. Thamrin Brothers Sentral Yamaha Bengkulu. Hence, the analysis method used Likert Scale.The obtained conclucions respondents agreed that leadership (X₁), reward (X₂) and punishment (X3) as independent variables have strongly influenced on employeeperformance (Y) as independent variablein PT. Thamrin Brothers Sentral Yamaha Bengkulu.